Simulation of Flooding in the Ky Lo River Basin, Phu Yen Province Under the Impacts of Climate Change and Sea Level Rise - Bach Tung, Nguyen; Dinh Duc, Dang; Ngoc Anh, Tran; Thanh Tung, Tran (VNU Journal of Science: Earth and Environmental Sciences, 2021)
This study attempts to develop the MIKE FLOOD model to simulate Ky Lo river flooding using two major floods in November 2009, November 2010 and survey results carried out in June and Octover 2019 by State Level Project ĐTĐL.CN.33/18 for calibration and validation. The results showed good agreements between simulated water level/discharge and observations. The model was then applied to simulate and assess floods in Ky Lo river basin under the impacts of climate change and sea-level rise until 2030 and 2070 using RCP 8.5 scenario issued by MONRE. The results showed that maximum flooding area downstream of Ky Lo river basin in 2030 was around 9.128 ha and in 2070 was 9.562 ha, corresponding to 100-year flood event, mostly concentrated in Chi Thanh, An Ninh Tay, An Cu, An Ninh Dong and An Chan communes of Tuy An district.